Effectiveness of routine tuberculosis education in a high-burden setting: A prospective observational cohort study - Tyler Scott Johnson; Leah Nanziri; Amanda J. Gupta; Joseph M. Ggita; Mari Armstrong-Hough; Irene Ayakaka; Sheela V. Shenoi; Achilles Katamba; J. Lucian Davis (PLoS ONE, 2026)
Background Low adherence to tuberculosis (TB) treatment remains a major driver of adverse health outcomes in high-burden countries. While guidelines recommend routine client education, its effectiveness and the knowledge constructs that influence adherence remain poorly defined. Methods We conducted a prospective cohort study of adults (≥18 years) initiating treatment for drug-susceptible TB in Kampala, Uganda. We assessed clients’ TB knowledge before and after routine education and at the two-week, two-month, and five-month follow-up visits. We recorded self-reported seven-day medication adherence at each visit and final treatment outcomes. We used paired t-tests to compare knowledge scores (0–100) before and after education. We constructed multivariable Poisson and logistic regression models to examine the association of knowledge with the outcomes of nonadherence and WHO-defined treatment success. Results We enrolled 80 participants (28% female; 36% living with HIV). Overall TB knowledge scores increased by 25 points (95% CI 22–28), from 53 to 78, yet only 9% achieved TB literacy (an overall TB knowledge score ≥90) after TB education, peaking at 18% at two weeks, before declining to just 3.6% at five months. Each 10-point increase in post-education knowledge was associated with a reduction in nonadherence of 15% (IRR 0.1 0.85; 95% CI 0.72–1.00, p = 0.048) at the two-week visit and 32% (IRR 0.1 0.68; 95% CI 0.50–0.89, p = 0.005) at the two-month visit. Ultimately, 71% completed treatment, but knowledge was not a significant predictor of treatment success (OR = 1.77, 95% CI 0.01–314.6, p = 0.83). Conclusions Routine client education significantly increased TB knowledge, yet less than 10% achieved TB literacy. Post-education knowledge was independently associated with better early adherence, highlighting the need for more robust education interventions to optimize TB treatment outcomes.